The urgency of finding new ways of communicating science while Antarctic ice is melting - Lorenzo, Cristian A.; Martinioni, Daniel Roberto
The warm temperatures of February 2020 renewed a global concern in the media about the future of the White Continent. Such temperatures raise new questions about our role as researchers. Scientists communicate the results to their peers through papers, but the impacts of climate change in Antarctica also require creative and effective ways of communication. Among different outreach activities related to Antarctica in Ushuaia, the “Café Antártico” (“Antarctic Coffee”) is an initiative performed by researchers in this Antarctic Gateway City. Three key ideas inspired the criteria for its organization since 2014: (I) interdisciplinary objectives in the invitation of speakers; (ii) itinerant venues in town; and (iii) general and interinstitutional public is invited. In doing so, we expect to shorten the distance between the people interested in Antarctica and those with Antarctic experience. Thus, we offer a meeting point beyond their public or private occupation to discover or deepen their knowledge about Antarctica. Although the “Café Antártico” is not an isolated action in science communication in Ushuaia, our efforts are not enough: climate change represents a new worldwide challenge to public engagement in science communication. This presentation aims to discuss experiences of public engagement in Antarctic science and articulate with other initiatives. Fil: Lorenzo, Cristian A. Universidad Nacional de Tierra del Fuego; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Martinioni, Daniel Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego; Argentina SCAR 2020: Antarctic Science - Global Connections Hobart Australia Scientific Committee on Antarctic Research